The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/jcm10215134
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoalbuminemia at Admission Is Strongly Associated with Worse Prognosis in Older Adults with SARS-CoV-2 Infection

Abstract: Serum albumin levels have been associated with prognosis in several conditions among older adults. The aim of this study is to assess the prognostic value in mortality of serum albumin in older adults with SARS-CoV-2 infection. Methods. Cohort observational study with consecutive older-adults (≥65 years old), with confirmed SARS-CoV-2 infection admitted to a university hospital between March–May 2020. A logistic regression model was fitted to assess the impact of albumin levels on in-hospital mortality adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
3
12
1
Order By: Relevance
“…A longitudinal cohort study where data of all consecutive patients admitted to the COVID-19 unit at Hospital del Mar, Barcelona, Spain for ≥48 h between March to May 2020 were collected. The study procedures have previously been described ( 3 , 14 ). As per protocol, the differentiation of CD4+ CD8+ T-cell subset was assessed in all admitted patients by flow cytometry at admission (day 1 of hospitalization), as well as a complete blood test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal cohort study where data of all consecutive patients admitted to the COVID-19 unit at Hospital del Mar, Barcelona, Spain for ≥48 h between March to May 2020 were collected. The study procedures have previously been described ( 3 , 14 ). As per protocol, the differentiation of CD4+ CD8+ T-cell subset was assessed in all admitted patients by flow cytometry at admission (day 1 of hospitalization), as well as a complete blood test.…”
Section: Methodsmentioning
confidence: 99%
“…Since its first detection in December of 2019, several prognosis factors have been described. Some of them are directly associated with uncontrolled immune response to the virus leading to a hyperinflammatory status, and some other ones such as hypoalbuminemia or myocardial injury, depend on the host clinical response ( 2 , 3 ). The impact of the virus in the immune system can be summarized as lymphopenia, which has been widely reported as a notable aspect of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been adduced as the basis for the altered plasma albumin status frequently documented among the SARS-CoV-2 infected patients in the literature [5][6][7][8][9]. Some investigators have suggested the amplified systemic inflammatory events frequently inherent among those infected [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated plasma albumin status among COVID-19 patients. However, most of these studies have been documented among the western populations and had included mostly patients with various comorbid conditions, gastrointestinal (GIT) features, and those on medications known to influence plasma albumin status [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, weight loss is rarely observed in patients with sepsis because intensive fluid resuscitation is the mainstay treatment in order to maintain blood pressure [ 4 ]. However, according to previous studies, weight gain or edema accompanied by excessive fluid resuscitation or hypoalbuminemia in septic patients significantly increases sepsis-related mortality [ 21 , 22 ]. Future studies evaluating the therapeutic benefits of early, high-dose DEX therapy in patients with sepsis are warranted in order to confirm the clinical utility of early, high-dose glucocorticoid therapy for the management of sepsis.…”
Section: Discussionmentioning
confidence: 99%